Decadal effects of thinning on understory light environments and plant community structure in a subtropical forest. Issue 10 (8th October 2018) - Tsai, Ho‐Chen; Chiang, Jyh‐Min; McEwan, Ryan W.; Lin, Teng‐Chiu
Abstract: Canopy‐opening disturbance such as thinning has immediate and substantive effects on understory microclimate and therefore the establishment and growth of understory plants. A large number of studies have reported the effects of thinning on tree growth, but few studies have examined long‐term effects of thinning on understory light environments and species and functional diversity of understory plants. Even less is known whether the change in understory plant community structure observed following canopy disturbance is short‐lived and would diminish as the canopy closes or a long lasting due to legacy effects. We examined the effects of an experimental removal of 25% and 50% of the woody vegetation on understory light availability and variability on understory plant community structure in a subtropical Cryptomeria japonica plantation nine years after the treatment. Differences in availability of understory light among treatments diminished nine years after the experimental vegetation removal (thinning), but variability of understory light was still two times higher in the thinned treatments than the un‐thinned control. Species diversity of dominant and common understory plants was lower in the control than in the two thinning treatments, which were not different from each other. Community species and functional composition were also different between the un‐thinned control and the two thinning treatments. The thinned plots had proportionally more individuals of grasses and forbs and fewer individuals of ferns. Our results indicate that the effects of thinning on understory light variability last longer than on light availability representing an important and long‐lasting alteration of resource heterogeneity. At both species and functional group levels, greater diversity and unique composition in the thinned treatments compared to undisturbed control suggest a link between resource heterogeneity and biodiversity in the forest understory or legacy effects associated with the thinning‐induced changes in understory plant community.